RADIOACTIVITY OF SOIL IN THE REGION OF THE TOWN OF NIŠ, SERBIA. Issue 4 (27th March 2019) - Manić, Vesna; Manić, Goran; Radojković, Branko; Vučić, Dušica; Nikezić, Dragoslav; Krstić, Dragana
Abstract: The concentration of radionuclides in samples of soil collected in the region of the town of Niš, was measured and presented in this paper. The naturally occurring radionuclides, 226 Ra, 232 Th and 40 K, were found in all samples. In many of them, 137 Cs was also measured, while the other artificial radionuclides were not detected. The measurements were carried out using the standard gamma spectroscopy system with high purity germanium (HPGe) detector. The results show that the average activity concentrations of 226 Ra, 232 Th, 40 K and 137 Cs are: 21, 26, 414 and 4.7, in Bq/kg, respectively. The sediment in the municipality spa Niška Banja exhibits a high content of 226 Ra, 573 Bq/kg. The outdoor dose rates, due to the gamma radiation of the ground, were also determined for all soils. The average absorbed dose rate in air was estimated to be 39 nGy/h, while the corresponding annual effective dose is 0.048 mSv.